Zagłada i krajobraz po Zagładzie w komiksowych kadrach - Forecki, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
Since the publication of two comic books entitled Maus by Art Spiegelman, the comics about the Holocaust became a separate category of graphic stories referring to history. The appearance of albums by Spiegelman may also be treated as a certain caesura on the Polish market of comics. Until that time, no Polish author of comic strips had even tried to come to grips with the topic of the Holocaust; even today they would rather avoid this topic. Taking no account of the reasons behind such abandonment, it is worth noting that Polish authors clearly gave ground to the creators from the West who, with mixed success, filled in this significant gap and their comics were later translated into Polish. The main purpose of the article is to show a panorama of comic books by Polish and Western authors, which have been published in Poland until now and, in various ways, touch upon the question of the Holocaust, thus becoming a part of a postcatastrophic discourse. The aim of the undertaken considerations is not solely the creation of the inventory but also a fragmentary but critical analysis of the contents of the mentioned comic strips.